(untitled) (Annals of Medical Research, 2021)
Aim: TROP2 is a member of the calcium signal converting gene family, which is highly expressed in various cancers. SOX10 is the nuclear transcription factor associated with the formation and development of various cancers. We investigated the importance of TROP2 and SOX10 in the differential diagnosis of tumoral lesions of the bladder. Materials and Methods: TROP2 and SOX10 expressions were evaluated by immunohistochemical method in 150 tumoral and 20 non-tumoral bladder tissues. Results: Strong staining with TROP2 was frequently seen in cases of papillary urothelial neoplasm with low malignant potential. There was no significant difference in the intensity of staining between the nontumoral group and the carcinoma groups, and between noninvasive carcinomas and invasive carcinomas. Conclusion: Although strong staining with TROP2 indicates tumoral development, widespread staining does not show this. Expression loss in TROP2 is observed in muscle invasive carcinomas. Strong and widespread (≥ 50%) TROP2 staining indicates papillary urothelial neoplasm with low malignant potential. Evaluation of this finding together with histomorphological findings may help to make an accurate diagnosis.